2022
DOI: 10.3390/info13030126
|View full text |Cite
|
Sign up to set email alerts
|

Navigations for Hospitality Human Resource Management Research: Observing the Keywords, Factors, Topics under the COVID-19 Pandemic

Abstract: The hospitality industry is one of the most affected by the pandemic, and because of its human close interaction and labor-intensive characteristics, it has left Human Resource Management (HRM) puzzles with organizations’ stabilization and recovery. This study aimed to summarize current research on hospitality HRM research outcomes and trends during the COVID-19 pandemic. Utilizing the PRISMA technique and NVivo software, 102 research articles were extracted and analyzed to highlight to overall achievement and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 58 publications
0
1
0
Order By: Relevance
“…Based on technology, some authors have developed the "Increasing Visitors Expectation Model" (ETEM), which examines how tourists' expectations for Environmentally Friendly Sustainable Operation (ESO) also apply to the tourism-related goods and services they purchase [13]. This is a difficult process of learning, training, and development, but many travelers (maybe on their first vacation abroad) will be delighted with the fundamental requirements of a good hotel and location at affordable prices.…”
Section: Evolving Tourist Expectation Model (Etem)mentioning
confidence: 99%
“…Based on technology, some authors have developed the "Increasing Visitors Expectation Model" (ETEM), which examines how tourists' expectations for Environmentally Friendly Sustainable Operation (ESO) also apply to the tourism-related goods and services they purchase [13]. This is a difficult process of learning, training, and development, but many travelers (maybe on their first vacation abroad) will be delighted with the fundamental requirements of a good hotel and location at affordable prices.…”
Section: Evolving Tourist Expectation Model (Etem)mentioning
confidence: 99%
“…The Marina Bay area, which is considered a global banking capital, has also been a tourist hub for the last three decades [25]. However, due to the COVID-19 pandemic, there was a significant decline in the tourism industry [31]. Especially, in the tourist hub in Singapore's Marina Bay area.…”
Section: Singapore's Marina Bay Area Luxury Hotelsmentioning
confidence: 99%
“…In the long run, this enhances business performance and growth (Balmer, 2022;Giertz, Hollebeek, Weiger, & Hammerschmidt, 2022). Conversely, it was observed that staff in the tourism sector are key determinants of the variables such as service quality, customer satisfaction and loyalty, competitive advantage and organizational performance (Abdiyev & Alimardonov, 2022;Kalla;Wang, Ban, Joung, & Kim, 2022). Also, it was found that the quality of human resources plays a crucial role in determining the quality, delivery, efficiency, and satisfaction of services offered (Marneros, Papageorgiou, & Efstathiades, 2022).…”
Section: Training Needs Assessment In the Tourism Industrymentioning
confidence: 99%